Protecting Libya's Archaeological Heritage - Bennett, Paul; Barker, Graeme (The African Archaeological Review, 2011)
Keywords: Archéologie – Djebel Nefousa

La moschea rupestre di Tnumayat (Gebel Garbi, Tripolitania, Libia) - Dell'Aquila, Franco; Fiorentino, Giuseppe; Bencini, Claudio (Opera Ipogea, 2011)
Wadi Adrar Foundation and Multidisciplinary Study Group “Berber Civility and Vernacolar Architecure” are performing survey missions since 2006 in the Jebel Gabi in Libya, addressed to study archaeological remnants of the ancient autochthonous civility once populating the tripolitanian mountain, to place artefacts in their historical context and finally to disseminate results. Architectural structures both constructed and digged into the rock were asessed, cave dwellings representing the majority of study cases, and showing a wide spectrum of models depending both on the various usage patterns befitting daily life, and on the geological structure of archaeological sites. Hitherto, Wadi Adrar Foundation and Multidisciplinary Study Group “Berber Civility and Vernacolar Ar chitecure” established cooperation toghether with italian Universities of Pisa and Florence, the Mediterra nean University, and with the Alrefak University of Tripoli, costituting working groups that studied, measu red and modeled several abandoned villages, Qasr, single housings and oil mills, all being both constructed or digged into the rock. In the present work the Rock Cave Mosque in Tnumayat is studied in detail, being situated in al-Khirba (the ruins) in the Kabaw neighbourhood. This individual artifact has been selected for the study as it represents an original example of Rock Cave Mosque showing fine digging technique and finely plaster bas-relief decorated interiors. A long inscription situated in the Dromos entrance trabeation allows both construction dating in 454 a.E.-1062 A.D. and customer Abd al-Malik identification. Interior is divided into three naves and a separate area reserved to women is identifiable
Keywords: Archéologie – Djebel Nefousa